New Biological Morphogenetic Methods for Evolutionary Design of Robot Bodies - Hockings, Nick; Howard, David (Frontiers in Bioengineering and Biotechnology, 2020)
We present some currently unused morphogenetic mechanisms from evolutionary biology and guidelines for transfer to evolutionary robotics. (1) DNA patterns providing mutation of mutability, lead to canalization of evolvable bauplans, via kin selection. (2) Morphogenetic mechanisms (i) Epigenetic cell lines provide functional cell types, and identification of cell descent. (ii) Local anatomical coordinates based on diffusion of morphogens, facilitate evolvable genetic parameterisations of complex phenotypes %clock and wavefront, multi-scale (iii) Remodelling in response to mechanical forces facilitates robust production of well integrated phenotypes of greater complexity than the genome. An approach is proposed for the tractable application of mutation-of-mutability and morphogenetic mechanisms in evolutionary robotics. The purpose of these methods, is to facilitate production of robot mechanisms of the subtlety, efficiency and efficacy of the musculoskeletal and dermal systems of animals.